Mortality Predictors in the Surgical Treatment of Active Infective Endocarditis - Oliveira,Jenny Lourdes Rivas de (2018)
Abstract Introduction: Active infective endocarditis is associated with high morbidity and mortality. Surgery is indicated in high-risk conditions, and the main determinants of mortality in surgical treatment should be evaluated. Objective: To identify mortality predictors in the surgical treatment of active infective endocarditis in a long-term follow-up. Methods: This prospective observational study involved 88 consecutive patients diagnosed with active infective endocarditis, who underwent surgery between January 2005 and December 2015. Fifty-eight (65.9%) patients were male, the mean age was 50.87±16.15 years. A total of 31 (35.2%) patients had a history of rheumatic fever; 48 (54.5%) had had heart surgery with prosthetic valve implantation; 45 (93.8%) had biological prosthetic valve endocarditis and 3 (6.3%) mechanical prosthetic valve; 40 (45.5%) patients had the disease in their native valve. The mean EuroSCORE II was 8.9±6.5%, and the main surgical indication was refractory heart failure in 38 (43.2%) patients. A total of 68 bioprosthesis (36 aortic, 32 mitral) and 29 mechanical prostheses (12 aortic, 17 mitral) were implanted and three mitral valve plasties performed. A total of 25 (28.4%) patients underwent double or triple valve procedures. Aortic annulus reconstruction by abscess was performed in 18 (20.5%) and six (6.81%) patients had combined procedure. The mean surgery time was 359±97.6 minutes. Results: The overall survival in up to a 10-year follow-up period was 79.5%. In the univariate analysis, the main mortality predictors were positive blood cultures (P=0.003), presence of typical microorganisms (P=0.008), most frequently Streptococcus viridans (12 cases; 25%); C-reactive protein (hazard ratio [HR] 1.034, 95% confidence interval [CI] 1.000 to 1.070, P=0.04); creatinine clearance (HR 0.977, 95% CI 0.962 to 0.993, P=0.005); length of surgery: every five minutes multiplies the chance of death 1.005-fold (HR 1.005, 95% CI 1.001 to 1.009, P=0.0307); age (HR 1.060, 95% CI 1.026 to 1.096, P=0.001); and EuroSCORE II (HR 1.089, 95% CI 1.030 to 1.151, P=0.003). Conclusion: A positive blood culture with typical microorganism, C-reactive protein, age, EuroSCORE II, total surgical time and the presence of postoperative complications were the major predictors of mortality and significantly impacted survival in up to a 10-year follow-up period.